Literacy and learning - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Bingley, U.K. : Emerald, 2010)
Among the most commonly reported characteristics of individuals with learning and behavioral disabilities are significant and persistent problems with literacy acquisition. Fortunately, applied research has revealed a number of methods for facilitating literacy learning among individuals with learning and behavioral disabilities. Included in this volume are chapters from a group of internationally-prominent authors, addressing important issues in the conceptualizing, assessing, and treating problems in literacy. In addition, current research in writing for students with learning and behavioral disabilities is described. A final chapter address the implications of research with exceptional individuals for general understanding of learning and cognition. This volume is intended to be of interest to clinicians, teachers, researchers, graduate students, and many others interested in literacy and learning of individuals with learning and behavioral disabilities.
Response to intervention : treatment validity and implementation challenges in the primary and middle grades / Stephanie Al Otaiba, Mary Beth Calhoon, Jeanne Wanzek -- The role of context in the assessment of 'unresponsiveness' within responsiveness-to-intervention : the 'relative slope-difference discrepancy model' (RSDDM) / Georgios D. Sideridis, Susana Padeliadu, Faye Antoniou -- Literacy supports for adolescent struggling readers : taking action through comprehension instruction / Michael Faggella-Luby, Patricia Sampson Graner -- Developmental dyslexia in a transparent orthography : a study of Spanish dyslexic children / Manuel Soriano, Ana Miranda -- Reading comprehension : unanswered questions and reading instruction challenges / Solveig-Alma Halaas Lyster -- A longitudinal study of the impact of effective beginning reading instruction for English learners : literacy, language, and learning disabilities / Ann W. Graves -- Writing : underutilized for young children with disabilities? / M. Susan Burns, Julie K. Kidd, Tamara Genarro -- Teaching students with LD to use reading comprehension strategies / Alison Gould Boardman, Janette K. Klingner, Amy L. Boelé, Elizabeth Swanson -- Persuading students with emotional disabilities to write : a design study -- Margo A. Mastropieri, Thomas E. Scruggs, Yojanna Cuenca-Sanchez, Nancy Irby, Sara Mills, Linda Mason, Richard Kubina -- Components affecting expressive writing in typical and disabled writers / Cesare Cornoldi, Francesco Del Prete, Anna Gallani, Francesco Sella, Anna Maria Re -- Dyslexia : a categorical falsehood without validity or utility / Simon Gibbs, Joe Elliott -- The study of human exceptionality : how it informs our knowledge of learning and cognition / Margo A. Mastropieri, Thomas E. Scruggs.
Print version record
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Special Education -- Social Disabilities; Education -- Special Education -- General; Teaching of students with specific learning difficulties -- needs; Teaching of students with emotional & behavioural difficulties; Literacy; Learning